Powers, Necessity, and Determinism. (September 2014) - Franklin, Christopher Evan
<x xml:space="preserve">Abstract</x> Stephen Mumford and Rani Lill Anjum have argued that a theory of free will that appeals to a powers‐based ontology is incompatible with causal determinism. This is a surprising conclusion since much recent work on the intersection of the metaphysics of powers and free will has consisted of attempts to defend compatibilism by appealing to a powers‐based ontology. In response I show that their argument turns on an equivocation of 'all events are necessitated'.